Pulmonary responses following cardiac rehabilitation and the relationship with functional outcomes in children and young adults with heart disease - Kershner, Cassidy E.; Hardie, William D.; Chin, Clifford; Opotowsky, Alexander R.; Aronoff, Elizabeth B.; Mays, Wayne A.; Knecht, Sandra K.; Powell, Adam W. (Frontiers in Surgery, 2024)
Introduction Patients with congenital heart disease (CHD) often have pulmonary abnormalities and exercise intolerance following cardiac surgery. Cardiac rehabilitation (CR) improves exercise capacity in patients with CHD, but minimal study has been performed to see if resting and dynamic pulmonary performance improves following CR in those with prior cardiac surgery. Methods This was a retrospective cohort study of all patients who completed ≥12 weeks of CR from 2018 through 2022. Demographic, cardiopulmonary exercise test (CPET), spirometry, 6-minute walk, functional strength measures, and outcomes data were collected. Data are presented as median[IQR]. A Student's t-test was used for comparisons between groups and serial measurements were measured with a paired t-test. A p < 0.05 was considered significant. Results There were a total of 37 patients [age 16.7 (14.2–20.1) years; 46% male] included. Patients with prior surgery (n = 26) were more likely to have abnormal spirometry data than those without heart disease (n = 11) (forced vital capacity [FVC] 76.7 [69.1–84.3]% vs. 96.4 [88.1–104.7]%, p = 0.002), but neither group experienced a significant change in spirometry. On CPET, peak oxygen consumption increased but there was no change in other pulmonary measures during exercise. Percent predicted FVC correlated with hand grip strength (r = 0.57, p = 0.0003) and percent predicted oxygen consumption (r = 0.43, p = 0.009). The number of prior sternotomies showed negative associations with both percent predicted FVC (r = −0.43, p = 0.04) and FEV1 (r = −0.47, p = 0.02). Discussion Youth and young adults with a prior history of cardiac surgery have resting and dynamic pulmonary abnormalities that do not improve following CR. Multiple sternotomies are associated with worse pulmonary function.